Impact on Car Ownership of Local Variation in Access to Public Transport - Graham Robert Crampton (European Regional Science Association (ERSA), 2006)
This paper reports on a project funded by the Volvo Research Foundations. It is international in nature and focuses on the impact of urban public transport, and light rail in particular, on restraining the growth of (or even reducing) local car ownership rates. The recent Censuses of the UK (2001) and France (1999) make these two countries particularly suitable, but the project examined other countries and urban transport systems too. We were especially interested in the `high quality' alternatives to light rail, including other urban rail, or enhanced forms of bus. Especially in Britain, the investment costs in new light rail systems have led to Government disquiet and reluctance to approve funding. The empirical work consists of econometric estimates using small area data, mainly from Censuses, reinforced by GIS mapping of urban transport access on the local small area. 300 metre and 600 metre zones of good access can then be used in the econometrics, alongside socioeconomic indicators of the economically active population. Results from a wide range of cities suggest that good access does indeed reduce car ownership below what would be expected given the local socioeconomic profile. These findings have important implications for environmental and transport policy
Keywords: 330